Modelling of vehicle motion control - Listopadskis, Narimantas (Lietuvos matematikos rinkinys, 2001)
The problem is to calculate the path trajectory and sequence of control signals for a vehicle following a wire in the floor. Motion of the vehicle is determined by system of differential equations. Fourth-order Runge–Kutta adaptive method was used for solving of the obtained system of the differential equations.